HPV-16 E2/E6 and POU5F1B as Biomarkers to Determine Cervical High-Grade Squamous Lesions and More - Chen L; Dong B; Gao H; Xue H; Pan D; Sun P (Dove Medical Press, 2020)
Lihua Chen,1,2,* Binhua Dong,2,3,* Hangjing Gao,2,3 Huifeng Xue,4 Diling Pan,5 Pengming Sun1– 3 1Department of Gynecology, Fujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China; 2Fujian Provincial Key Laboratory of Women and Children Major Disease, Fujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China; 3Laboratory of Gynecologic Oncology, Fujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China; 4Medical Center of Cervical Disease and Colposcopy, Fujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China; 5Department of Pathology, Fujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pengming SunFujian Provincial Maternity and Child Hospital, Affiliated Hospital of Fujian Medical University, 18 Daoshan Road, Fuzhou 350001, Fujian, People’s Republic of ChinaTel +86-591-87558732 (Lab Office)Fax +86-591-87551247Email sunfemy@hotmail.comPurpose: Human papillomavirus-16 (HPV-16) is the most carcinogenic HPV genotype. This study aimed to evaluate the clinical value of POU5F1B and HPV-16-E2/E6 by cervical cytology specimens to predict the cervical intraepithelial neoplasia two grade and more (CIN2+).Methods: Finally, 248 patients with HPV-16 single infection were enrolled. Using cytology specimen by real-time quantitative PCR (qPCR), POU5F1B mRNA and HPV-16-E2/E6 were detected. The relationship of POU5F1B, HPV-16-E2/E6 and CIN2+ were analyzed, and the optimal cut-off values of POU5F1B and HPV-16-E2/E6 to predict CIN2+ were calculated.Results: The mean HPV-16-E2/E6 decreased signiﬁcantly with cervical lesions development, especially compared with CIN2+ (p< 0.05). And the POU5F1B demonstrated higher expression in CIN2+ than that of normal cervical tissue and CIN1 (p< 0.05). What is more, POU5F1B was negatively correlated with HPV-16-E2/E6. It demonstrated that the area under the receiver operating characteristic curve (AUC) for POU5F1B (0.9058) was higher than that for HPV-16-E2/E6 (0.8983), and the sensitivity and specificity of POU5F1B in the diagnosis of CIN2+ were higher than HPV-E2/E6. Furthermore, it demonstrated that the POU5F1B had the highest odds ratio (OR= 16.84; 95% CI (8.00– 35.46)) for the detection of CIN 2+.Conclusion: HPV-16-E2/E6≤ 0.6471 or POU5F1B≥ 1.0310 in cervical exfoliated cells can be used as a reliable predictor of CIN2+. POU5F1B can be used as a new auxiliary biomarker to determine the HPV infection status and a reliable predictor of CIN2+. The expression of POU5F1B≥ 1.0310 had the highest OR for the detection of CIN2+.Keywords: cervical intraepithelial neoplasia, human papillomavirus type 16, POU5F1B, HPV integration, HPV-E2/E6